The effectivity of binahong (anredera cordifolia (ten.) steenis) leaves extract for growth inhibition of streptococcus mutans in oral cavity - Gostry A. Dohude; Frisca CM. Ginting (DiscoverSys Inc., 2021)
Objective: This research was conducted to determine the effectiveness of binahong (anredera cordifolia (ten.) steenis) leaves extract in inhibiting the streptococcus mutans growth.Material and Methods: The study is true experimental laboratories with posttest-only control group design. The study sample used was binahong leaves and streptococus mutans bacteria that were multiplied in Microbiology Laboratory of the Faculty of Pharmacy, Universitas Sumatera Utara. This study used seven treatment groups namely, 75%, 50%, 25%, 12.5%, 6.25% binahong leaves extract, amoxicillin (positive control) and Dimethyl Sulfoxide (DMSO) (negative control). Testing the treatment group for the streptococcus mutans was carried out using the Kirby-Bauer disk diffusion method with four repetitions. Extract was done by maceration using 96% ethanol solvent.Results: Indicate that the binahong leaves extract can inhibit the growth of streptococcus mutans which can be seen from the clear zone formed on paper discs that have been given binahong leaves extract with a concentration of 75%, 50%, 25%, 12.5%, 6.25%, along with amoxicillin and dimethylsulfoxide/DMSO. The results also showed a significant difference in diameter of the inhibition zone from each treatment group (p <0.005).Conclusion: Binahong leaves extract has antibacterial ability because it can inhibit the growth of Streptococcus mutans in the oral cavity and compared to other concentrations, 75% concentration is more effective in inhibiting the growth of streptococcus mutans in the oral cavity.